KONSEP DAN IMPLEMENTASI KELUARGA IDEAL DALAM PERSPEKTIF MAQĀŞID SYARİ’AH IBN ‘ASYUR - Mujib Rahman Salim (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2020)
The family has been around for thousands of years. As the smallest unit in society, it has survived and is able to grow in line with the needs of its people. The rights and obligations of individuals in a unique (and culturally related) family make the family deserve to be an endless unit of research analysis. The conclusion of this study is the concept of Maqāṣid Syarī'ah in the family according to Ţahir Ibn 'Asyur: the family is the basis of human civilization and the orderliness of the order of society. In connection with Ibn 'Asyur's view of the application of the Maqāṣid Syarī'ah in the family: Islām Regulates the distribution of sexual desires, for there are adverse and destructive effects if not regulated. Meanwhile, custody in marriage is a form of protection against both parties. Wedding announcements generally aim to achieve two main goals: caring and mutual respect. The great concern of the Syari'ah regarding the protection of the noble is to prevent all the causes of the disputes it causes